Individual and collective climate control in aircraft cabins. (10th July 2006) - Jacobs, P.; De Gids, W.F.
A new concept for aircraft cabin climatisation has been developed in which the seat is the main Indoor Air Quality (IAQ) and temperature control system for the passengers containing provisions for local supply and local exhaust of air. Direct supply of clean outside air in the breathing zone, through the headrest of the seat, yields a high ventilation efficiency enabling e.g. local humidification and, depending on disturbances of the cabin ventilation system, 57-96% shielding against contaminants from other passengers. Exhaust of 0-2dm³/s per seat involves a cooling load of 0-20 W, which is up to 20% of the metabolism of a seated person. Control of cabin temperature takes place at two levels: 1. individual control; the passenger influences his seat surface temperature by varying the exhaust flow; and 2. on cabin scale, the control is based on a 'voting' system based on the average individual exhaust flows.